More Than the Code: Learning Rules of Rejection in Writing Programs. - TENENBERG, JOSH; ROTH, WOLFF-MICHAEL; CHINN, DONALD; JORNET, ALFREDO; SOCHA, DAVID; WALTER, SKIP (Communications of the ACM, 2018)
The article discusses an exercise in a computer science class to discover tacit rules of computer software programming as a social practice. Topics include the involvement of students in participative code writing, the relation between teacher and student in the exercise, and the learnability of rules for the rejection of software code.